ANALISIS PEMBIASAAN DISIPLIN SISWA TERHADAP DIMENSI GOTONGROYONG PADA PROFIL PELAJAR PANCASILA - MUBAROK, HUSNIL; WIDIYONO, AAN (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This study aims to observe and analyze the dimension of mutual cooperation in schools, both its implementation and the supporting and inhibiting factors in the implementation of the mutual cooperation dimension. The elements of mutual cooperation consist of: 1) The formation of positive dependence between each individual involved, 2) individual responsibility, 3) the parties involved interact with each other personally, 4) skills to work together, 5) evaluating the group process. Observing the research results that have been presented, the conclusion that can be drawn is that the cultivation of the character of gotong royong at SDN 3 Ngasem Batealit is carried out through a number of activities such as daily garbage, class picket, community service every Friday, Friday infaq and P5 (Pancasila student profile strengthening project). In addition to this, teachers also provide positive role models by participating in gotong royong (mutual cooperation) such as participating in garbage picking and Friday clean-up activities, working together to clean the school environment, always giving alms when an infaq program is held on Fridays, and becoming the main activist for the implementation of P5. Researchers also found that there are a number of things that become supporting factors for the implementation of mutual cooperation character development activities, namely the diligent personality of children, role models from teachers, caring parents, and the creation of cooperation between teachers and the school in pursuing various programs to develop mutual cooperation attitudes. While the obstacles faced in developing mutual cooperation attitudes are the existence of ignorant, selfish and lazy student personalities, habituation that is not consistently implemented, and the availability of school facilities that are very lacking. ABSTRAKPenelitian ini bertujuan untuk mengamati dan menganalisa dimensi gotong royong yang ada disekolah baik implementasinya maupun faktor pendukung dan faktor penghambat dalam pelaksanaan dimensi gotong royong. Unsur-unsur gotong royong terdiri dari : 1) Terbentuknya ketergantungan positif antar setiap individu yang terlibat, 2) tanggungjawab perorangan, 3) pihak-pihak yang terlibat saling berinteraksi secara personal, 4) keahlian untuk bekerja sama, 5) pengevaluasian proses kelompok. Mengamati hasil riset yang sudah dipaparkan, konklusi yang dapat diambil ialah penanaman karakter gotong royong di SDN 3 Ngasem Batealit dilakukan melalui sejumlah kegiatan seperti sampah setiap hari, piket kelas, kerja bakti setiap hari Jum’at, infaq hari jumat dan P5 (projek penguatan profil pelajar Pancasila). Di samping hal tersebut, guru ikut pula dalam memberikan keteladanan positif dengan turut berpartisipasi dalam gotong royong seperti ikut dalam aktivitas pungut sampah dan Jumat bersih, bekerja bakti membersihkan lingkungan sekolah, senantiasa bersedakah ketika diadakan program infaq di hari Jumat, serta menjadi penggiat utama pelaksanaan P5. Peneliti juga menemukan adanya sejumlah hal yang menjadi faktor pendukung pelaksanaan kegiatan pengembangan karakter kegotongroyongan yakni kepribadian anak yang rajin, teladan dari guru, orang tua yang perhatian, dan terciptanya kerja sama antara guru dengan pihak sekolah dalam mengupayakan berbagai program untuk menumbuhkembangkan sikap gotong royong. Sedangkan kendala yang dihadapi dalam pengembangan sikap gotong royong adalah adanya kepribadian siswa yang cuek, egois dan malas, pembiasaan yang kurangnya terlaksana secara konsisten, serta ketersediaan fasilitas sekolah yang sangat kurang.